Development of a Waste Pollution Module using the Argument Driven Inquiry (ADI) Model for Students - Diartika, Eka Imbia Agus; Sueb, Sueb; Al-Muhdar, Mimien Henie Irawati; Suhadi, Suhadi (Biosfer: Jurnal Tadris Biologi, 2024)
This research aims to develop a waste pollution module using the Argument Driven Inquiry (ADI) model. The module was developed using the ADDIE development model which consists of five stages, namely analysis, design, development, implementation, and evaluation. The validity of this development module refers to the results of validation by validators who are teaching materials experts, material experts and field practitioners. The practicality of this module refers to the results of assessments by users (students). The research results show that the module developed meets validity and practicality.ABSTRAK: Penelitian ini bertujuan untuk mengembangkan modul pencemaran sampah dengan model Argument Driven Inquiry (ADI). Modul dikembangkan dengan model pengembangan ADDIE yang terdiri dari lima tahap, yaitu analysis, design, development, implementation, dan evaluation. Kevalidan modul hasil pengembangan ini mengacu pada hasil validasi oleh validator ahli bahan ajar, ahli materi, dan praktisi lapangan. Kepraktisan modul ini mengacu pada hasil penilaian oleh pengguna (mahasiswa). Hasil penelitian menunjukkan bahwa modul yang dikembangkan telah memenuhi kevalidan  dan kepraktisan.